STUDI MANAJEMEN LAYANAN MAKANAN INSTITUSI PONDOK PESANTREN DARUL AMAN MAKASSAR - Anni Safitri; Irviani Ibrahim; Syarfaini Syarfaini; Syamsul Alam; Muhammad Rusmin (Universitas Islam Negeri Alauddin Makassar, 2021)
Background: Food management system is a series of activities ranging from menu planning to food distribution to consumers to achieve optimal status. There are 23 Islamic boarding schools in Makassar City with 7,600 students consisting of 4,006 female students and 3594 male students.Objective:This study aims to determine the implementation of food at the Darul Aman Islamic Boarding School in Makassar.Method: This research is a research qualitative with an approach descriptive using primary and secondary data. Determination of informants using purposive sampling method consisting of 3 key informants and 8 regular informants. Data were collected by in-depth interviews and processed using content analysis after which triangulation was carried out.Result: Based on interviews and observations, it was found that the annual expenditure budget planning was 230 / month. SAOP foodstuff procurement, an acceptance process that includes inspection or research based on details of daily orders or invoices. The storage of food ingredients uses the FIFO method, the process of preparing food ingredients includes standard recipes and equipment preparation. Processing of food ingredients based on ingredients ordered by the head of the kitchen without a menu cycle. The distribution of food uses a combination of centralized-decentralized systems.Conclusion: The implementation of hygiene and sanitation in the process of organizing food has not been maximized, starting from preparation to distribution is not following Permenkes No. 1204 / Menkes / SK / X / 2004 and Health Decree of the Republic of Indonesia Number 942 / Menkes / SK / 2003. It is recommended that foundations and pesantren pay more attention to the completeness of equipment and materials in the kitchen, as well as hygiene and sanitation so that food administration runs optimally